A DSGE analysis on the optimal monetary policy amidst natural disasters - Lim, Dickson A. (Animo Repository, 2016)
The Philippines is one of the countries in the ASEAN region to be regularly hit by natural disasters and these catastrophic events entail adverse macroeconomic impact to the economy. Unfortunately, there has been minimal research done on the monetary aspect of natural disasters. The goal of this study is to determine the optimal monetary policy rule amidst natural disasters. Since natural disasters create inflationary pressure to the economy and the succeeding foreign aid received by country leads to Dutch disease effects, the tradeoff in monetary policy response to natural disasters needed to be examined. This study has found that an exchange rate intervention policy is optimal relative to inflation targeting as a monetary response to an unanticipated natural disaster shock.